2016
DOI: 10.1093/jxb/erw013
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between 2-Cys peroxiredoxins and ascorbate in autophagosome formation during the heat stress response inSolanum lycopersicum

Abstract: Highlight2-Cys peroxiredoxins fulfil a pivotal role in heat stress tolerance in Solanum lycopersicum via interactions with ascorbate-dependent pathways and autophagy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 51 publications
1
27
0
Order By: Relevance
“…Use of TEM is a valid and important method for the quantitative analysis of autophagosomes (Cheng et al ., ; Klionsky et al ., ). Our transgenic lines had more autophagosomes than WT under drought stress, a finding that was in line with the decreased accumulation of oxidized insoluble proteins under drought stress.…”
Section: Discussionmentioning
confidence: 99%
“…Use of TEM is a valid and important method for the quantitative analysis of autophagosomes (Cheng et al ., ; Klionsky et al ., ). Our transgenic lines had more autophagosomes than WT under drought stress, a finding that was in line with the decreased accumulation of oxidized insoluble proteins under drought stress.…”
Section: Discussionmentioning
confidence: 99%
“…Our group previously described that heat stress induces the expression of autophagy‐related (ATG) genes and the accumulation of autophagosomes in tomato plants . Virus‐induced gene silencing (VIGS) of several tomato ATGs resulted in an increased sensitivity to heat stress, suggesting the involvement of autophagy in the heat stress response in tomato plants . Recently, Wang et al.…”
Section: Discussionmentioning
confidence: 99%
“…42 Virusinduced gene silencing (VIGS) of several tomato ATGs resulted in an increased sensitivity to heat stress, suggesting the involvement of autophagy in the heat stress response in tomato plants. 4 Recently, Wang et al also reported that melatonin enhanced the occurrence of autophagy in response of the Arabidopsis to methyl viologen (MV)-induced oxidative stress. 37 Here, we found that the expression of several ATGs and the production of autophagosomes were further induced by melatonin pretreatment and overexpression of ASMT under heat stress ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autophagosomes assemble in the cytosol to remove oxidatively modified structures as large as organelles. Interestingly, impaired chloroplast antioxidant function is sufficient to trigger this pathway (Cheng et al, 2016).…”
Section: Longer Term Signaling Downstream Of Rosmentioning
confidence: 99%